Compromised Dynamic Cerebral Autoregulation in Patients With Idiopathic Rapid Eye Movement Behavior Disorder: A Case-Control Study Using Transcranial Doppler - Lv, Shan; Wang, Zan; Sun, Xin; Jin, Hang; Liu, Jia; Deng, Fang; Lv, Yudan; Jia, Meiyan; Guo, Zhen-Ni; Yang, Yi (Frontiers in Psychiatry, 2020)
Background: Patients with idiopathic rapid eye movement (REM) behavior disorder (IRBD) have been suggested to exhibit altered cerebral perfusion and abnormal cerebral blood flow, which imply a possibility of cerebral autoregulation (CA) impairment. We aimed to investigate the dynamic cerebral autoregulation (dCA) in patients with IRBD during wakefulness and explore the correlations between dCA parameters and clinical measurements. Methods: We assessed the dCA capability of 30 patients with IRBD and 36 sex- and age-matched healthy controls using transcranial Doppler and finger plethysmography. CA function was evaluated by transfer function analysis based on spontaneous oscillation of cerebral blood flow and arterial blood pressure. Transfer function parameters (phase difference and gain) were used to quantify the CA. Results: There were no significant differences between the right and left middle cerebral artery (MCA) dCA parameters (phase difference and gain) of both groups. Patients with IRBD had significantly lower phase difference compared with the healthy controls, indicating their impaired CA capability. Besides, the value of gain in patients with IRBD was higher than the healthy controls, but the difference did not reach statistical level. Conclusions: CA function is compromised in the patients with IRBD during wakefulness, which might be an intermediate link between IRBD and neurological symptoms.